Forecasting land use and land cover change as a tool for optimising adaptation to climate change: Examples of selected Second-Tier Cities of the V4 Group - Feltynowski, Marcin; Rzeńca, Agnieszka; Palma, Agnieszka (Bulletin of Geography. Socio-economic Series, 2024)
Second-tier cities are an important element in the socio-economic development of each country, including V4 countries. The result is a dynamic change in land use/cover patterns. The article analyses the possibility of using Markov chains to predict changes in land use. The results show that it is possible to use the Markov chains method in proper decision-making in land-use policy, which is combined with the stimulation of sustainable land use. The research results show that Markov chains can be an important tool to guide cities’ climate policies and build their capacity to adapt to climate change.